The use of language learning strategies in general - Siladi Vasyl; Szilágyi László; Сіладі Василь (Видавництво МДУ, 2019)
Abstract. The purpose of the study is to emphasize the importance of strategies for learning a foreign language and its teaching. The work generalizes available information from the strategies of language learning, defines the concept of a language learning strategy, and outlines the taxonomy of language learning strategies proposed by leading researchers in this field. The author takes into account the role of a teacher in teaching strategies and presents a number of problems for further study of language learning strategies.
https://msu.edu.ua/wp-content/uploads/2019/05/%D0%97%D0%B1%D1%96%D1%80%D0%BD%D0%B8%D0%BA-%D1%82%D0%B5%D0%B7-%D0%B4%D0%BE%D0%BF%D0%BE%D0%B2%D1%96%D0%B4%D0%B5%D0%B9.pdf
https://opac3.brff.monguz.hu:443/en/record/-/record/bibBRF00008133
Keywords: learning strategy; direct; indirect; technique; taxonomy; personality; motivation; self-esteem; life experience; learning style; excitement; anxiety